Practical management of concomitant acute heart failure and worsening renal function in the emergency department. (August 2018) - Ferreira, João Pedro; Chouihed, Tahar; Nazeyrollas, Pierre; Levy, Bruno; Seronde, Marie F.; Bilbault, Pascal; Braun, François; Roul, Gérald; Kénizou, David; Zannad, Noura; Girerd, Nicolas; Rossignol, Patrick
Abstract : Worsening renal function (i.e. any increase in creatinine or decrease in the estimated glomerular filtration rate) is common in patients admitted for acute heart failure in the emergency department. Although worsening renal function (WRF) has been associated with the occurrence of dismal outcomes, this only appears to be the case when associated with clinical deterioration. However, if the clinical status of the patient is improving, a certain increase in serum creatinine may be acceptable. This WRF, which is not associated with clinical deterioration or adverse outcomes (e.g. during treatment up-titration), has been referred to as 'pseudo-WRF' and should not detract clinicians from targeting 'guideline-recommended' therapies. This is an important message for emergency physicians to pursue diuretics as long as signs of pulmonary congestion persist to improve the clinical status of the patient. In the present review, we aim to provide clinicians in acute settings with an integrative and comprehensive approach to cardiorenal interactions in acute heart failure.